POLA ASUH IBU YANG MENIKAH USIA DINI DENGAN STATUS GIZI BALITA (USIA 0-59 BULAN) DI DESA DASAN TAPEN KECAMATAN GERUNG LOMBOK BARAT 2016 - M Karjono; Murtiana Ningsih (JURNAL SANGKAREANG MATARAM, 2016)
Children under five years is one or troeble nutrition group, so that in this period they depend on their mothers’ rearing. Early married women will be difficult to understand nutrition problem, especially in fulfilling the nutrition. Base on preliminary study at Dasan tapen village on women who married early found that in the amount of 60% mothers who gave MP-ASI on aged less than 6 months and 70% mothers who gave snack with frequency >3 times in a day. This study aimed to know the relationship between mothers’ rearing who married in the early aged and nutrition status on children under five years aged 0-59 months at Dasan Tapen village district Wes Lombok regency in 2016. This study in observational analytic with cross sectional approach. Population is all mothers who married in the early aged (< 20 years old) and have children under five years. Samples are taken by total sampling technique in the amount of 45 respondents. Result of the study showed nutrition ststus of children under five years old based on Body Weight/Age index in the amount 0f 73.3% have good nutrition status, 24.4% have under nutrition status and 66.7% normal category, 28.9% short and other 4.4% very short. Rearing pattern of mothers who married in the early aged got 42.2% not good enough and 24.4% good. There is a significant relationship toward nutrition status on children under five years old and the most affect in rearing pattern on eating with Correlation Coefficient in the amount of 0.63. The conclusion is rearing pattern of mothers who married in the early aged tends to have good children under five whereas rearing pattern not good enough affect bad bad nutrition status. It is suggested to mothers who married in the early aged and own children under five years to increase their knowledge about nutrition necessity fot children under five years by participating in Posyandu to increase nutrition status for their children under five years.